PENGARUH PENERAPAN LKS BERBASIS MODEL CREATIVE PROBLEM SOLVING PADA MATERI BUNYI, CAHAYA DAN ALAT OPTIK TERHADAP HASIL BELAJARA IPA SISWA KELAS VIII SMPN 3 PADANG - Riri Camara Putri; Syakbaniah Syakbaniah; Ratnawulan Ratnawulan (Universitas Negeri Padang, 2015)
One causes of low science learning is low of ability in problems solving. For motivate student increase of ability in problems solvier needfull ability in creative thinking especially for contents of sounds, lighting, and optic instruments. The purpose of this research was to determine the learning result of the science students and to investigate the effect student worksheet based models creative problem solving to the leaning result of science students grade VIII at SMPN 3 Padang. Type of research was quasi experimental research with randomized control group only design. The population in this research were the students grade VIII SMPN 3 Padang who were registered in the 2014/2015 academic year. Sampling technique was cluster random sampling. There were three instruments in this research, tose are test sheet of cognitive domain, observation sheet of affective domain, and performance sheet of pschycomotor domain. Based on the data analysis could be presented the result of this research. Results of research show the average of science learning outomes are 69,44 and 67,68 at cognitive domain, 77,50 and 72,27 at affective domain, 84,53 and 78,94 at pschycomotor domain. By using t analysis, tcount > ttable so alternatif hipotesis is accepted. The use student worksheet based models creative problem solving has given significant effect toward Physics studies result of students grade VIII SMPN 3 Padang at 0,05 significant level